2006
DOI: 10.1088/0953-2048/20/1/l01
|View full text |Cite
|
Sign up to set email alerts
|

High critical current density under magnetic fields in as-grown MgB2thin films deposited by molecular-beam epitaxy

Abstract: As-grown MgB2 thin films were prepared by a MBE method under the conditions of low temperature, low deposition rate and high vacuum for applications in electric devices. The MgB2 thin films deposited on MgO and Ti buffered ZnO substrates have considerably higher Jc under magnetic fields among MgB2 thin films reported before. The value of Jc for the MgB2 thin film deposited on Ti buffered ZnO has been 5.8 × 105 A cm−2 at 10 K, 5 T in the magnetic field applied parallel to the c axis. In the angular depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Thus we can conclude that the MgO plates are oriented with (0 0 1) MgO planes parallel to (0 0 1) MgB2 MgB 2 planes. This mutual orientation of cubic MgO and hexagonal MgB 2 phases has already been observed and discussed [25][26][27][28][29][30][31]. 1 0 MgO [29].…”
Section: Grains and Inter-grain Secondary Phase Layerssupporting
confidence: 63%
See 1 more Smart Citation
“…Thus we can conclude that the MgO plates are oriented with (0 0 1) MgO planes parallel to (0 0 1) MgB2 MgB 2 planes. This mutual orientation of cubic MgO and hexagonal MgB 2 phases has already been observed and discussed [25][26][27][28][29][30][31]. 1 0 MgO [29].…”
Section: Grains and Inter-grain Secondary Phase Layerssupporting
confidence: 63%
“…The film was polycrystalline and it did not have any preferential in-plane orientation, only strong [0 0 1] MgB2 out-of-plane texture. Some other authors also published c-oriented MgB 2 thin film on (0 0 1) MgO substrate without any additional information about the in-plane orientation[26][27][28]. Tian et al showed clear epitaxial growth of (…”
mentioning
confidence: 99%
“…High quality MgB 2 thin films are prepared by molecular beam epitaxy (MBE) [2] and electron beam evaporation (EBE) [3]. As-grown MgB 2 thin films deposited at low temperature by MBE and EBE have a high critical current density J c .…”
Section: Introductionmentioning
confidence: 99%
“…We achieved a value of T C = 37 K by the MBE method, which is the same as that with HPCVD. Fujiyoshi et al report that the J C of the MgB 2 films on the Ti buffer layer is higher than that of MgB 2 on the substrates [16]. Therefore, the pinning force due to the grain boundaries at the MgB 2 film on the Ti buffer layer is stronger than that of other films.…”
Section: Introductionmentioning
confidence: 99%